IMPLIKASI PEMBERLAKUAN PERDA SYARI’AT TERHADAP IDEOLOGI NEGARA INDONESIA - Arfiansyah Arfiansyah (Islam Futura, 2015)
Since the downfall of Soeharto’s New Order regime in 1999, Indonesia political orientation drastically changed. President Baharuddin Jusuf (BJ) Habibie enacted number of laws that changed the face of Indonesian politics from authoritarianism to democracy. One of the laws was Law No. 22 of 1999 on Regional government, which was amended by Law No. 32 of 2004 on Regional Government. The law brought Indonesia from centralism politics to fully decentralism. All individuals and groups, mainly marginalized Muslim groups during the New Order regime, have taken the best of the shift to force the implementation of Syaria law in Indonesia by advocating the enactment of numbers of Syariat inspired regional regulations (Perda berbasis Syariat) in tens of provinces. The Perda soon became controversial and triggered debate among Muslims themselves. Even some worried if the Perda would change Indonesian constitution and ideology from secular to Islamic one. Using qualitative approach and analyzing Indonesian political preference at national-wide, this article argues that the Perda would not affect Indonesian constitution and ideology. Even large number of Indonesians likely accept the development of the Perda as part of development of democracy in Indonesia.